A Call for Gender-Inclusive Global Health Strategies. (November 2017) - Rovito, Michael J.; Leonard, Brandon; Llamas, Ramon; Leone, James E.; Talton, Walker; Fadich, Ana; Baker, Peter
The WHO's "Global Strategy for Women's, Children's, and Adolescents' Health 2016-2030" (GS-WCAH 2016-2030) is a comprehensive plan developed to improve the lives of women, children, and adolescents. Due to the success in the creation, ratification, and advocacy of the GS-WCAH 2016-2030, the clear health outcome disparities between males and females, and the general absence of male health from existing policies and sponsored programs, it is time now to develop a global strategy specifically drafted to improve the lives of men and boys. The following commentary provides three points for why a male-oriented program, like the GS-WCAH 2016-2030, should be created: (a) health outcomes disparities, (b) economic impact of poor male health, and (c) fathers' role in promoting the health of women, children, and adolescents. Implications for how male health can be incorporated into future projects and priorities are provided, as well as advocacy for overall gender-inclusivity in regard to global public health efforts.